2020
DOI: 10.3390/ijms21228809
|View full text |Cite
|
Sign up to set email alerts
|

Repositioned Drugs for Chagas Disease Unveiled via Structure-Based Drug Repositioning

Abstract: Chagas disease, caused by the parasite Trypanosoma cruzi, affects millions of people in South America. The current treatments are limited, have severe side effects, and are only partially effective. Drug repositioning, defined as finding new indications for already approved drugs, has the potential to provide new therapeutic options for Chagas. In this work, we conducted a structure-based drug repositioning approach with over 130,000 3D protein structures to identify drugs that bind therapeutic Chagas targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 113 publications
0
16
0
Order By: Relevance
“…Still, as a screening approach, our structure-based method has very high success rates. In previous studies, the approach demonstrated to predict 5–10% binders [63] , [29] , [18] , which is superior to high-throughput screenings. In the present study, two out of six hit compounds actually bind LRRK2 G2019S, which corresponds to a success rate of 33%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, as a screening approach, our structure-based method has very high success rates. In previous studies, the approach demonstrated to predict 5–10% binders [63] , [29] , [18] , which is superior to high-throughput screenings. In the present study, two out of six hit compounds actually bind LRRK2 G2019S, which corresponds to a success rate of 33%.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction feature was defined by the combination of two non-covalent interactions within an angle and distance range. If a particular interaction feature was present in the interaction pattern, the respective bin was set to 1, otherwise, it was set to 0, as already described in [29] , [18] . The interaction fingerprints are available from PharmAI (Dresden, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To approaching the multidrug treatment of the T. cruzi infections we selected the polymerases inhibitor 4-Fluorquinolone Ofloxacin [136137] and the Azidothymidine reverse transcriptase inhibitor [114, 115], and the lead nitro heterocycle Benznidazole. The treatment of the acutely T. cruzi- infected BALB/c mice with the Benznidazole curtailed the parasitemia at the 15 th day of the drug administration, whereas the flagellates lasted for 40 days in the blood of the infected-untreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Campthothecin Inhibits PP1 and PP2 at serine/threonine phosphatases and cell growth inhibition 50 [129,130] Cycloheximide Inhibits p38 activated protein kinase (MAKPK) a nd cell entry at G2/M phase 5 [131,132] Etoposide Down regulate polymerase II at S-G2 phases and prevents cell division 50 [133,134] Ofloxacin 4-Fluorquinolone inhibits polymerase at G2/M phase, and apoptosis 30 [135,136] Praziquantel Isoquinolone inhibits serine/threonine kinase (PI3-k) polymerases I and II 46 [137][138][139] Staurosporine Protein kinases inhibitor (A, C, CAM and PI3K) prevents cell growth at G1 check point 9 [140,141] *Each drug suspension (µg/100 µL) in 0.15M NaCl used in the cytotoxic in vitro assays. µg…”
Section: Polymerase Inhibitorsmentioning
confidence: 99%